Novel chemical inhibitor against SOD1 misfolding and aggregation protects neuron-loss and ameliorates disease symptoms in ALS mouse model - Woo, Tae-Gyun; Yoon, Min-Ho; Kang, So-mi; Park, Soyoung; Cho, Jung-Hyun; Hwang, Young Jun; Ahn, Jinsook; Jang, Hyewon; Shin, Yun-Jeong; Jung, Eui-Man; Ha, Nam-Chul; Kim, Bae-Hoon; et al. (Communications biology, 2021)
Amyotrophic Lateral Sclerosis (ALS) is a fatal neurodegenerative disease characterized by selective death of motor neurons. Mutations in Cu, Zn-superoxide dismutase (SOD1) causing the gain of its toxic property are the major culprit of familial ALS (fALS). The abnormal SOD1 aggregation in the motor neurons has been suggested as the major pathological hallmark of ALS patients. However, the development of pharmacological interventions against SOD1 still needs further investigation. In this study, using ELISA-based chemical screening with wild and mutant SOD1 proteins, we screened a new small molecule, PRG-A01, which could block the misfolding/aggregation of SOD1 or TDP-43. The drug rescued the cell death induced by mutant SOD1 in human neuroblastoma cell line. Administration of PRG-A01 into the ALS model mouse resulted in significant improvement of muscle strength, motor neuron viability and mobility with extended lifespan. These results suggest that SOD1 misfolding/aggregation is a potent therapeutic target for SOD1 related ALS. With ELISA-based screening, Woo et al. identify a new small molecule, PRG-A01, which can block the misfolding/aggregation of SOD1 or TDP-43 in a human neuroblastoma cell line. Its use in a mouse model of ALS results in improvement of muscle strength, motor neuron viability and mobility, highlighting its therapeutic potential in ALS.